Research on Environmental Quality Evaluation System of Coordinated Development of the Beijing-Tianjin-Hebei Region. Issue 1 (June 2020) - Hao, C X; Ge, C Z; Qin, J L; Chen, Z W; Zhou, Q; Qu, A Y; Peng, C; Li, N; Dong, Z F; Hu, Rui
Abstract: Since the coordinated development plan of Beijing-Tianjin-Hebei region was put forward, environmental protection and pollution control have become the primary breakthrough of coordinated development. The ecological environment problem in Beijing- Tianjin-Hebei region has been the bottleneck factor restricting the integrated development. It is of great significance for environmental protection and economic development to establish a coordinated assessment mechanism for ecological environment quality in Beijing-Tianjin- Hebei region. This study analyzed the progress and effectiveness of the assessment of ecological environment quality in Beijing-Tianjin-Hebei region, analyzed the problems and challenges in the assessment of ecological environment in Beijing-Tianjin-Hebei region, and put forward some suggestions on the establishment of the mechanism of joint environmental prevention and control under the coordinated development of Beijing-Tianjin-Hebei region.